(untitled) (De Musica, 2024)
Fauré’s music is still today the subject of many misunderstandings and a general devaluation both by listeners of classical music, by performers and, obviously, by music critics. Situated between the end of the 19th and the beginning of the 20th century, his production is imbued with the complexities and contradictions of this period. But how is it a reflection of this? In other words, how is it possible to approach this "closed garden" hermeneutically without getting lost in ambiguity? This article is an opportunity to reflect again, in light of the centenary of his death (1924), on the French composer and on a certain inability of musical criticism to frame his values. In what sense can Fauré’s work be defined as "modernist"? Using the thought of the critic Antoine Compagnon as a reading prism, but also the philosophical interpretation of Jankélévitch, we will attempt to define some traits of Fauré’s production. Particular attention is paid to the experience of listening to Fauré.